Glacial Aerodynamic Roughness Estimates: Uncertainty, Sensitivity, and Precision in Field Measurements. Issue 2 (5th February 2020) - Chambers, Joshua R.; Smith, Mark W.; Quincey, Duncan J.; Carrivick, Jonathan L.; Ross, Andrew N.; James, Mike R.
Abstract: Calculation of the sensible and latent heat (turbulent) fluxes is required in order to close the surface energy budget of glaciers and model glacial melt. The aerodynamic roughness length, z 0, is a key parameter in the bulk approach to calculating sensible heat flux; yet, z 0 is commonly considered simply as a tuning parameter or generalized between surfaces and over time. Spatially and temporally distributed observations of z 0 over ice are rare. Both direct (from wind towers and sonic anemometers) and indirect (from microtopographic surveys) measurements of z 0 are subject to sensitivities and uncertainties that are often unstated or overlooked. In this study, we present a quantitative evaluation of aerodynamic profile‐based and microtopographic methods and their effect on z 0 using data collected from Storglaciären and Sydöstra Kaskasatjäkkaglaciären, Tarfala Valley, Arctic Sweden. Aggressive data filters discard most of the wind tower data but still produce realistic z 0 values of 1.9 mm and 2 mm. Despite uncertainty introduced by scale and resolution dependence, microtopographic methods produced estimates of z 0 comparable to wind tower values and those found on similar surfaces. We conclude that (1) in the absence of direct turbulent flux measurements from sonic anemometers, the profile and microtopographic methods provide realistic z 0 values, (2) both 2D and 3D microtopographic methods are dependent on scale, resolution, and the chosen detrending method, and (3) careful calibration of these parameters could enable glacier‐wide investigations of z 0 from remotely sensed data, including those increasingly available from satellite platforms. Key Points: Sensitivities and uncertainties in glacial aerodynamic roughness reviewed and analyzed using new field data Wind profile and microtopographic methods provide realistic values of z0 in absence of more robust eddy covariance data Despite scale/resolution dependency, microtopographic estimates show good agreement with profiles and could be used to upscale studies